The 3D-Language Acquisition Test and the Mentally Retarded - Kamalini Pillai (Journal of All India Institute of Speech and Hearing, 1970)
The 3D-LAT was administered to 45 moderately retarded children, to study their performance on it and to make inferences regarding the language behaviourof retarded children.